NGOs in Local Social Policy: A Study of Social Welfare Centers in Silesia Voivodeship - Faliszek, Krystyna (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Collaboration of local governmental structures with the non-governmental sector in the field of social policy plays an important role in increasing the effectiveness and efficiency of social welfare interventions. Both on the side of public institutions and on the side of non-governmental organizations, it is possible to pinpoint obstacles that stand in the way of effective and efficient interventions. The place where these impediments surface are social welfare centers in small communities. The aim of this article is to present, based on the results of a series of short-term pilot surveys, a snapshot of collaboration efforts between social welfare centers in Silesia Voivodeship and non-governmental organizations. The Author’s intention was to illustrate how the scope and depth of these collaborations vary depending on the size of the community. Study results reveal that small and large communities differ markedly not only in social welfare, but also how the relationships between local governments and NGOs are conceptualized and built.